1998
DOI: 10.1023/a:1006154108619
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Converging data from epidemiological and biological research implicate insulin-like growth factor (IGF) physiology in the regulation of prostate epithelial cell proliferation and in the pathophysiology of prostate cancer. This review (1) outlines elements of IGF physiology, (2) reviews recent evidence that circulating IGF-I level is related to risk of prostate cancer, (3) provides a hypothesis concerning the biological basis for the relationship between IGF-I level and risk of prostate cancer, (4) discusses IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(23 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…This will lead to an increase of bioavailable IGFs, allowing them to bind and activate type 1 IGF receptor (48,51,67) and indirectly modulate cell survival, mitogenesis, and differentiation. By this way, hK5 might play a role in tumorigenesis (67,68) and particularly in prostate cancer progression (69).…”
Section: Discussionmentioning
confidence: 99%
“…This will lead to an increase of bioavailable IGFs, allowing them to bind and activate type 1 IGF receptor (48,51,67) and indirectly modulate cell survival, mitogenesis, and differentiation. By this way, hK5 might play a role in tumorigenesis (67,68) and particularly in prostate cancer progression (69).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that PSA may act as a tumor suppressor, a negative regulator of cell growth, and an apoptotic molecule [33,34,35], whereas, others suggest that PSA may, through its serine protease activity, promote tumor progression and metastasis [36,37,38]. The precise relationship between the reported functions of PSA in prostate cancer cells in vitro and the biological role of PSA as a serine protease in human prostate cancer in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various suggested mechanisms by which AR may be reactivated in a low androgen environment (7), signaling by growth factors, especially insulin-like growth factor 1 (IGF1), is reportedly of significant importance (8 -11). High IGF1 serum levels are correlated with an increased risk of PC (8,9), whereas IGF1 enhances AR transactivation under very low or absent androgen levels (12,13) and promotes PC cell proliferation (10). Recent studies have also revealed that high serum insulin levels are associated with an increased incidence of PC (14,15), although there is a lack of mechanistic studies implicating insulin signaling in the regulation of AR function.…”
Section: Androgen Receptor (Ar)mentioning
confidence: 99%